Son of Sam and his Legislative Offspring: The Constitutionality of Stripping Criminals of Their Literary Profits - Young, Alan N. (1988)
We have seen in recent years a growing demand to recognize the victims’ rights and needs. In Canadian jurisdictions this has resulted in the introduction of victims-witness assistance programs that are designed to provide support to a victim of crime throughout the court process. Compensation boards have also been set up to provide financial remuneration w those who have suffered injury or loss at the hands of the perpetrator of the crime. In the United States, however, a more aggressive scheme for providing victim redress has been adopted by a number of the state legislatures. These Son of Sam laws, named for the convicted New York killer David Berkowitz, operate to confiscate profits reaped by offenders who choose to recount their criminal exploits. The author examines the development of these laws in the United States and discusses the advantages and disadvantages of such a scheme in the Canadian legal context. This discussion turns on the proposition that royalty stripping violates the right to freedom of expression, subject to the reasonable limit clause found in section I of the Charter of Rights and Freedoms. Three potential arguments under clause 1 are discussed in detail: institutional restrictions necessitated by incarceration; victims' rights to receive compensation; and the principle of unjust enrichment. The author concludes that the Son of Sam laws have a disproportionate effect on freedom of expression and that they are not the best vehicle for furthering victims' rights